Modern targets for multilevel orders for social upbringing - Zulfia A. Aksyutina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The study of social upbringing has resumed recently and so far no complete target has been identified in scientific research. Based on the fact that there are social orders at the state, public and personal levels, an attempt is made to identify them. Social order regarding social education should be considered as a system for solving problems related to socialization and professionalization, solved by social and educational institutions. The presented review reflects the tendencies of scientific researches of targets for upbringing in domestic and foreign studies. Note that such studies are rare. The most priority aspects of research on the goals of education have been identified, reflecting a greater bias towards goal-setting in education, and educational goals remain insufficiently researched. The modern target thesis in education is for a person to be happy. The aim of the study was to identify targets for different levels of social orders for social education. It was assumed that social orders for social upbringing at different levels have homogeneity. The study of the general public was conducted to identify social orders at the societal and personal levels, and at the state level, social orders were studied through the analysis of regulatory documents. Differences in the formation of social orders for social education at the levels of the individual, society and the state are revealed, which is due to the social roles, functions and goals that various social institutions perform. In conclusion, it is indicated that the hypothesis put forward is partially confirmed. The materials of the study are of interest to the general pedagogical community concerning the understanding of the representation of social orders for social upbringing, in determining their leading guidelines for designing the process in question.